SARS-CoV-2 Spike Protein and Long COVID—Part 2: Understanding the Impact of Spike Protein and Cellular Receptor Interactions on the Pathophysiology of Long COVID Syndrome - Bruno Pereira de Melo; Jhéssica Adriane Mello da Silva; Mariana Alves Rodrigues; Julys da Fonseca Palmeira; Angélica Amorim Amato; Gustavo Adolfo Argañaraz; Enrique Roberto Argañaraz (Viruses)
SARS-CoV-2 infection has had a significant impact on global health through both acute illness, referred to as coronavirus disease 2019 (COVID-19), and chronic conditions (long COVID or post-acute sequelae of COVID-19, PASC). Despite substantial advancements in preventing severe COVID-19 cases through vaccination, the rise in the prevalence of long COVID syndrome and a notable degree of genomic mutation, primarily in the S protein, underscores the necessity for a deeper understanding of the underlying pathophysiological mechanisms related to the S protein of SARS-CoV-2. In this review, the latest part of this series, we investigate the potential pathophysiological molecular mechanisms triggered by the interaction between the spike protein and cellular receptors. Therefore, this review aims to provide a differential and focused view on the mechanisms potentially activated by the binding of the spike protein to canonical and non-canonical receptors for SARS-CoV-2, together with their possible interactions and effects on the pathogenesis of long COVID.